Measuring Melanoma Nanomechanical Properties in Relation to Metastatic Ability and Anti-Cancer Drug Treatment Using Scanning Ion Conductance Microscopy - Emily Woodcock; Peter V. Gorelkin; Philip S. Goff; Christopher R. W. Edwards; Yanjun Zhang; Yuri Korchev; Elena V. Sviderskaya (Cells, 2023)
A cell’s mechanical properties have been linked to cancer development, motility and metastasis and are therefore an attractive target as a universal, reliable cancer marker. For example, it has been widely published that cancer cells show a lower Young’s modulus than their non-cancerous counterparts. Furthermore, the effect of anti-cancer drugs on cellular mechanics may offer a new insight into secondary mechanisms of action and drug efficiency. Scanning ion conductance microscopy (SICM) offers a nanoscale resolution, non-contact method of nanomechanical data acquisition. In this study, we used SICM to measure the nanomechanical properties of melanoma cell lines from different stages with increasing metastatic ability. Young’s modulus changes following treatment with the anti-cancer drugs paclitaxel, cisplatin and dacarbazine were also measured, offering a novel perspective through the use of continuous scan mode SICM. We found that Young’s modulus was inversely correlated to metastatic ability in melanoma cell lines from radial growth, vertical growth and metastatic phases. However, Young’s modulus was found to be highly variable between cells and cell lines. For example, the highly metastatic cell line A375M was found to have a significantly higher Young’s modulus, and this was attributed to a higher level of F-actin. Furthermore, our data following nanomechanical changes after 24 hour anti-cancer drug treatment showed that paclitaxel and cisplatin treatment significantly increased Young’s modulus, attributed to an increase in microtubules. Treatment with dacarbazine saw a decrease in Young’s modulus with a significantly lower F-actin corrected total cell fluorescence. Our data offer a new perspective on nanomechanical changes following drug treatment, which may be an overlooked effect. This work also highlights variations in cell nanomechanical properties between previous studies, cancer cell lines and cancer types and questions the usefulness of using nanomechanics as a diagnostic or prognostic tool.